Analysis of Teacher-Created Songs and The Value of Character Education AT KB IT H. Djoepri Jepara - Evitasari, Dwi ana; Syakir Syakir; Suharto Suharto (Universitas Negeri Semarang, 2023)
Analysis Of Teacher- Created Songs And The Value Of Character Education AT KB IT H. Djoepri Jepara. Analyses the primary aspect, constituting: To begin with, the structure and form of music; Secondly, an analysis of the significance of character education as expressed in a composed song. Utilising a qualitative analytic research design and a multidisciplinary approach, these two facets of the Ministry of National Education Research and Development Centre For Curriculum are meticulously examined in relation to the fundamental form and structure of music. This writing's data collection method includes interviews, documentation studies, literature reviews, and observational studies. This study employs the triangulation method to assess the validity of the data. Triangulation entails the subsequent stages: data reduction, data analysis, inference, and data presentation. Result of research: Initially, the musical structure of the song